A NEW APPROXIMATION IN DETERMINATION OF ZONATION BOUNDARIES OF IGNIMBRITE BY GROUND PENETRATING RADAR: KAYSERI, CENTRAL ANATOLIA, TURKEY - Koralay T.; Kadioglu S.; Kadioglu Yu.K. (My University, 2007)
Ground penetrating radar (GPR) method is used as a tool to identify the zonation boundaries in ignimbrite series through their columnar section. Ignimbrites can be classified in terms of welding degree, colour, texture and mineralogical compositions. The research area comprises a part of İncesu (Kayseri) ignimbrite at Central Anatolia, Turkey. This ignimbrite is divided into three levels and each level has clear differences in terms of macroscopic and microscopic views. This paper presents the results of an application of GPR for the determination of zonation boundary within the ignimbrite flow unit in the view of their textural and petrological features. RAMAC CU II equipment was used with 250MHz shielded antenna on parallel ten profiles to observe the physical difference among the ignimbrite levels of the study area. Two levels out of three have been defined at the İncesu ignimbrite and supported by field geology and petrographical studies. The first level, which is extremely fractured structure, is about 1.5m thick and matches with middle level of the İncesu ignimbrite. The second level has an average 50–75cm thickness and matches with lower level of the ignimbrite. In this manner, vertical lithological variations should be taken into consideration during petrological investigation of the ignimbrites.
Keywords: Ignimbrite; Zonation boundary; Ground penetrating radar (GPR); Petrography